The Philosophy of "Habonaron Do Bona" as Anti-Corruption Conduct in the Simalungun Tribe Society - Purba, Indra Gunawan (JURNAL AKTA, 2023)
Corruption is an extraordinary crime, so this crime is already an enemy of all countries. Many countries later ratified the United Nations Convention Against Corruption (UNCAC). Indonesia is one of them through Law Number 7 of 2006. Corrupt behavior later made it more difficult to eradicate corruption. Corrupt behavior exists in each individual person. It may not be realized that the behavior seems to be normal and eventually it is considered normal and, unfortunately, it is then considered correct. Even though culture or religion never teaches things that make one's actions despicable. Habonaron Do Bona is the philosophy of life of the Simalungun tribe, one of the ethnic groups of thousands of ethnic groups in Indonesia. The Simalungun tribe holds firmly and instills this philosophy into the community so that every person who has a Simalungun ethnicity is embedded in the philosophy of Habonaron Do Bona in his heart, whether consciously or unconsciously this philosophy becomes the life guide for people who are Simalungun in living their lives and lives. This philosophy later became the jargon of Simalungun Regency, one of the districts in the North Sumatra Province of Indonesia, where the Simalungun tribe lives and originates. Habonaron Do Bona is a philosophy that is defined as "truth is the basis of everything" which means that the philosophy of Habonaron Do Bona is anti-untrue teachings, which if it is associated with corrupt behavior, the philosophy of Habonaron Do Bona is anti-corruption teachings that have been passed down by the ancestors of the Simalungun tribe which is interesting to research. Of course, this research will discuss how the philosophy of "Habonaron Do Bona" as a form of anti-corruption behavior held by the Simalungun tribe community has been inherited by the predecessors of the Simalungun tribe.